Consensus on Environmentally Sustainable Oral Healthcare A Joint Stakeholder Statement - Shellard, Ian J. (White Rose University Press, 2022)
The Oral Healthcare community, including clinical professionals and industry, acknowledges the shared responsibility to deliver products and interventions that improve oral health in a more sustainable manner. To deliver this, the community is working in alignment with the UN Sustainable Development Goals. Key to establishing this collaborative stakeholder consensus is a deep contextual understanding of the challenge. This is achieved through a comprehensive account of the levels of awareness of the environmental impacts, the challenges to resolve these impacts together with the drivers and opportunities to promote sustainable practices. This report concludes with a strategic action framework that makes specific recommendations and identifies best practice to achieve these goals. The promotion of excellent oral healthcare and the development of a circular economy are core to this strategy. Additionally, it is also important to recognise the opportunities to collaborate across the sector, and throughout supply chains, to develop and promote sustainable practices to achieve meaningful and measurable environmental outcomes in the sector. In this context, the FDI World Dental Federation convened the development of this volume, Consensus on Environmentally Sustainable Oral Healthcare: A Joint Stakeholder Statement. This consensus statement brings together a global coalition of stakeholders, representing all aspects of industry, health professionals, experts, legislative authorities and governments. The statement uses a truly collaborative, multi-stakeholder approach to identify the major challenges facing oral healthcare, the complex drivers that underpin current behaviours and practices, and the best opportunities to improve and deliver sustainable oral healthcare for people and the planet. Concluding with an impactful and robust strategic action plan that crosses all boundaries, the statement identifies a series of actions and recommendations for best practice that address the sustainability issues facing the whole sector.